A mechatronic shape display based on auxetic materials - steed, Anthony; Ofek, Eyal; Sinclair, Mike; Gonzalez Franco, Mar (Nature Communications, 2021)
Shape displays enable people to touch simulated surfaces. A common architecture of such devices uses a mechatronic pin-matrix. Besides their complexity and high cost, these matrix displays suffer from sharp edges due to the discreet representation which reduces their ability to render a large continuous surface when sliding the hand. We propose using an engineered auxetic material actuated by a smaller number of motors. The material bends in multiple directions, feeling smooth and rigid to touch. A prototype implementation uses nine actuators on a 220 mm square section of material. It can display a range of surface curvatures under the palm of a user without aliased edges. In this work we use an auxetic skeleton to provide rigidity on a soft material and demonstrate the potential of this class of surface through user experiments.